Recurrent NR3C1 Aberrations at First Diagnosis Relate to Steroid Resistance in Pediatric T-Cell Acute Lymphoblastic Leukemia Patients. Issue 1 (21st January 2021) - van der Zwet, Jordy C. G.; Smits, Willem; Buijs-Gladdines, Jessica G. C. A. M.; Pieters, Rob; Meijerink, Jules P. P.
Abstract : Supplemental Digital Content is available in the text. Abstract : The glucocorticoid receptor NR3C1 is essential for steroid-induced apoptosis, and deletions of this gene have been recurrently identified at disease relapse for acute lymphoblastic leukemia (ALL) patients. Here, we demonstrate that recurrent NR3C1 inactivating aberrations—including deletions, missense, and nonsense mutations—are identified in 7% of pediatric T-cell ALL patients at diagnosis. These aberrations are frequently present in early thymic progenitor-ALL patients and relate to steroid resistance. Functional modeling of NR3C1 aberrations in pre-B ALL and T-cell ALL cell lines demonstrate that aberrations decreasing NR3C1 expression are important contributors to steroid resistance at disease diagnosis. Relative NR3C1 messenger RNA expression in primary diagnostic patient samples, however, does not correlate with steroid response.